2018
DOI: 10.1002/advs.201800080
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Evolution of Carbon Structures Underpinned by Temperature‐Induced Intermediate of Chloride for Sodium‐Ion Batteries

Abstract: Different dimensions of carbon materials with various features have captured numerous interests due to their applications on the tremendous fields. Restricted by the raw materials and devices, the controlling of their morphology is a major challenge. Utilizing the catalytic features of the intermediates from the low‐cost salts and polymerization of 0D carbon quantum dots (CQDs), 0D CQDs are expected to self‐assemble into 1/2/3D carbon structures with the assistance of temperature‐induced intermediates (e.g., Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 141 publications
(100 reference statements)
2
56
0
Order By: Relevance
“…The Nyquist plots reveal that the pristine resistance of CF is smaller than that of other samples in Figure F, derived from the rich pristine defects. With the cycling, gradually reduced resistances were found on the NF cell, as shown in Figure S12 in the Supporting Information, originating from the CE < 100%, demonstrating that the residual sodium ions could improve the conductivity . Moreover, in Figure G, the sharpest peaks of NF is observed, matching well with its high crystalline.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The Nyquist plots reveal that the pristine resistance of CF is smaller than that of other samples in Figure F, derived from the rich pristine defects. With the cycling, gradually reduced resistances were found on the NF cell, as shown in Figure S12 in the Supporting Information, originating from the CE < 100%, demonstrating that the residual sodium ions could improve the conductivity . Moreover, in Figure G, the sharpest peaks of NF is observed, matching well with its high crystalline.…”
mentioning
confidence: 75%
“…In high‐resolution TEM (HRTEM) images of the as‐obtained samples, it is found that the samples were encapsulated in the high‐ordered graphitic carbon (0.37 nm), while they were embedded into the amorphous carbon (0.38) . The thickness of graphitic carbon layer was about CF‐2 (5.1 nm), NF‐2 (5.3 nm), and MF‐2 (9.3 nm), resulting from the catalytic characteristic of Co/Ni/Mn for carbon . These advantages above could give rise to the rapid rate of ion transfer and the alleviation of volume expansion.…”
mentioning
confidence: 99%
“…The XRD measurement of all samples are exhibited in Figure 2A. The broad peaks located at 23 • and inconspicuous peaks centered at 43 • are perceived, indicating that all the samples are in amorphous constructions maintained few regions of crystallinity (Hou et al, 2015(Hou et al, , 2017Ge et al, 2018;Zou et al, 2018;Wu et al, 2019). More detailer pore structures of the samples are collected by the nitrogen adsorption/desorption measurements in Figures 2B,C. The isotherms of all DSPCs exhibit a combination of I-type and IV-type isotherm characteristics at a relative pressure >0.4, suggesting that both micropores and mesopores exist.…”
Section: Resultsmentioning
confidence: 99%
“…The current density of CV curves was increased gradually as the sweep rate increase from 0.2 to 1.4 mV s −1 . Usually, the relationship with the sweep and current is presented in Equation i = aνb where i is the current density, a and b are the parameters, v stands the scan rate. The capacity contributions mainly divided into two parts: the intercalation process is controlled by diffusion when the b‐value is closing to 0.5, while the capacitive process as the b‐value is near to 1.…”
Section: Resultsmentioning
confidence: 99%